Key Disease Mechanisms Linked to Amyotrophic Lateral Sclerosis in Spinal Cord Motor Neurons - Bottero, Virginie; Santiago, Jose A.; Quinn, James P.; Potashkin, Judith A. (Frontiers in Molecular Neuroscience, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with no modifying treatments available. The molecular mechanisms underpinning disease pathogenesis are not fully understood. Recent studies have employed co-expression networks to identify key genes, known as “switch genes”, responsible for dramatic transcriptional changes in the blood of ALS patients. In this study, we directly investigate the root cause of ALS by examining the changes in gene expression in motor neurons that degenerate in patients. Co-expression networks identified in ALS patients’ spinal cord motor neurons revealed 610 switch genes in seven independent microarrays. Switch genes were enriched in several pathways, including viral carcinogenesis, PI3K-Akt, focal adhesion, proteoglycans in cancer, colorectal cancer, and thyroid hormone signaling. Transcription factors ELK1 and GATA2 were identified as key master regulators of the switch genes. Protein-chemical network analysis identified valproic acid, cyclosporine, estradiol, acetaminophen, quercetin, and carbamazepine as potential therapeutics for ALS. Furthermore, the chemical analysis identified metals and organic compounds including, arsenic, copper, nickel, and benzo(a)pyrene as possible mediators of neurodegeneration. The identification of switch genes provides insights into previously unknown biological pathways associated with ALS.